SEPARATION OF Fe (III), Cr(III), Cu(II), Ni(II), Co(II), AND Pb(II) METAL IONS USING POLY(EUGENYL OXYACETIC ACID) AS AN ION CARRIER BY A LIQUID MEMBRANE TRANSPORT METHOD - La Harimu; Sabirin Matsjeh; Dwi Siswanta; Sri Juari Santosa (Universitas Gadjah Mada, 2010)
Fe (III), Cr(III), Cu(II), Ni(II), Co(II), and Pb(II) metal ions had been separated using poly(eugenyl oxyacetic acid) as an ion carrier by bulk liquid membrane transport method. The effect of pH, polyeugenyl oxyacetic acid ion carrier concentration, nitric acid concentration in the stripping solution, transport time, and metal concentration were optimized. The result showed that the optimum condition for transport of metal ions was at pH 4 for ion Fe(III) and at pH 5 for Cr(III), Cu(II), Ni(II), Co(II), and Pb(II) ions. The carrier volumes were optimum with concentration of 1 x 10-3 M at 7.5 mL for Cr(III), Cu (II), Ni(II), Co(II) ions and at 8.5 mL for Fe(III) and Pb(II) ions. The concentration of HNO3 in stripping phase was optimum at 2 M for Fe(III) and Cu(II) ions, 1 M for Cr(III), Ni(II) and Co(II) ions, and 0.5 M for Pb(II) ion. The optimum transport times were 36 h for Fe(III) and Co(II) ions, and 48 h for Cr(III), Cu (II), Ni(II), and Pb(II) ions. The concentration of metal ions accurately transported were 2.5 x 10-4 M for Fe(III) and Cr(III) ions, and 1 M for Cu (II), Ni(II), Co(II), and Pb(II) ions. Compared to other metal ions the transport of Fe(III) was the highest with selectivity order of Fe(III) > Cr(III) > Pb(II) > Cu(II) > Ni(II) > Co(II). At optimum condition, Fe(III) ion was transported through the membrane at 46.46%.